Technology Integration for Promoting Deep Learning in EFL Contexts - Ramli Ramli; Woro Kusmaryani (Script Journal: Journal of Linguistics and English Teaching, 2026)
Background This study explored how an EFL lecturer understands deep learning as a pedagogical approach, how digital and AI-supported tools are integrated into EFL speaking instruction, and what challenges emerge when these tools are used in a classroom located in the Indonesia-Malaysia border area. Methodology This study employed an interpretive qualitative case-study design at the English Education Department of Universitas Borneo Tarakan, North Kalimantan, Indonesia. The participant was one purposively selected EFL lecturer who taught a speaking class and had already used digital and AI-supported applications in classroom practice. Data were collected through a semi-structured interview, four classroom observations, field notes, and video recordings of classroom activities. Findings The findings suggested that technology-supported activities appeared to create classroom conditions associated with deep learning. Students participated in group discussions, short writing activities, spontaneous speaking, oral presentations, and communicative tasks related to familiar contexts such as tourism, travel, hotel booking, and personal experiences. The lecturer used digital and AI-supported tools, including Duolingo, Elsa Speak, Cake, Busuu, Blooket, speech-to-text tools, QuillBot, and Grammarly, to support vocabulary learning, pronunciation practice, speaking rehearsal, gamified review, language feedback, revision, and learner engagement. These tools extended classroom practice and made learning more meaningful and enjoyable. However, the findings also indicated that technology did not automatically create deep learning. Its value depended on the lecturer's pedagogical guidance and on how the tools were connected to speaking tasks, reflection, and communicative purposes. Conclusion In this observed case, technology integration appeared to support active participation, contextualized language use, learner autonomy, reflection, and positive engagement in an EFL speaking classroom. At the same time, some students tended to rely too quickly on AI tools for ready-made answers, highlighting the need for teacher mediation, digital literacy, and ethical awareness. Technology can enrich EFL learning when it is used with a clear pedagogical purpose, but it should not replace students' own thinking or the teacher's instructional role. Originality This study provided context-specific evidence from a higher-education EFL classroom in the Indonesia-Malaysia border area. It demonstrated how one lecturer interpreted and enacted technology integration to support learning conditions associated with deep learning in speaking instruction.